1999
DOI: 10.1107/s090744499900339x
|View full text |Cite
|
Sign up to set email alerts
|

Determining the molecular-packing arrangements on protein crystal faces by atomic force microscopy

Abstract: Previous atomic force microscopy (AFM) studies and periodic bond-chain (PBC) analyses of tetragonal lysozyme crystals have suggested that the (110) face consists of chains of molecules related to one another by 43 axes parallel to the crystal face. In this study, high-resolution AFM images of the (110) face were obtained and analyzed in order to verify this prediction. A computer program was employed which constructs the theoretical AFM image corresponding to a specific crystallographic molecular-packing arran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 26 publications
2
27
0
Order By: Relevance
“…From such images, it may be possible to deduce packing arrangements or even molecular orientations. Li et al (1999) and Kuznetsov et al (1999a), for example, used AFM to analyze packing arrangements on the faces of lysozyme and thaumatin crystals, respectively, and from these deduced the ordered pathways for molecule incorporation. Because height information is preserved, enantiomorphic space groups can be resolved.…”
Section: Sample Preparation and Data Acquisitionmentioning
confidence: 99%
“…From such images, it may be possible to deduce packing arrangements or even molecular orientations. Li et al (1999) and Kuznetsov et al (1999a), for example, used AFM to analyze packing arrangements on the faces of lysozyme and thaumatin crystals, respectively, and from these deduced the ordered pathways for molecule incorporation. Because height information is preserved, enantiomorphic space groups can be resolved.…”
Section: Sample Preparation and Data Acquisitionmentioning
confidence: 99%
“…A distinctly different process occurred which involved the restructuring of the surface lattice of a transition particle. Restructuring of ordered, or partially ordered, surfaces is known to occur in other systems, most prominently, the surfaces of growing crystals [39][40][41] and the surfaces of micelles. 42,43 If such restructuring can take place in the transformation of the virions and particles studied here, then it may very well occur in natural virus assembly processes as well.…”
Section: Particle Transitionsmentioning
confidence: 99%
“…It was also shown that the 4 3 helix is formed by strong bonds and that crystal growth is likely to proceed in a manner which preserves this unit's structure. These predictions were con®rmed by AFM scans which showed that the (110) faces are formed by planes corresponding to this construction (Konnert et al, 1994;Li, Perozzo et al, 1999). Further con®rmation was provided by a recent study of the crystal-packing arrangement employing a somewhat different approach (Strom & Bennema, 1997a,b).…”
Section: Growth Mechanism and Surface Morphologymentioning
confidence: 81%
“…Growth units of at least tetramer size are needed to preserve the completeness of the 4 3 helices in the crystal, which is a requirement for both the (110) and (101) faces (Nadarajah & Pusey, 1996;Strom & Bennema, 1997a,b). As mentioned previously, only complete 4 3 helices were found on the (110) face in AFM investigations (Konnert et al, 1994;Li, Perozzo et al, 1999). This requirement also rules out larger crystallizing units for this face, as this would have resulted in the growth steps being multi-layered.…”
Section: Growth Mechanism and Surface Morphologymentioning
confidence: 99%
See 1 more Smart Citation